History of the Development of Philosophy and Science in the Greek and Islamic Era - Junida Fitriani Sitorus; Salminawati Salminawati; Siska Diyah Syahfitri; Ida Marina Harahap (Universitas Muhammadiyah Enrekang, 2023)
This research examines the historical development of the philosophy of education and science during the Greek and Islamic periods, two historical epochs that significantly influenced the evolution of thought and the conception of science. In classical Greek times, philosophers such as Plato and Aristotle contributed profound thoughts regarding education and science. The primary focus was on exploring the fundamental concepts of education, character formation, and the development of scientific thought. A shift in intellectual focus occurred during the Islamic Golden Age, where Greek knowledge was inherited and enriched by Muslim scholars such as Ibn Sina and Ibn Khaldun. Islamic thought played a crucial role in integrating philosophy, education, and science, with the application of scientific methods, rationality, and ethics as integral parts of the educational approach. This research employs a historical analysis method to trace the development of ideas and major contributions of figures in both periods. The results of the study highlight the evolution of education and science concepts from classical Greece to the Islamic era, indicating a transfer of intellectual ideas and values that laid the foundation for the development of modern science and education. It is hoped that a profound understanding of the history of the development of the philosophy of education and science in both periods can provide critical insights into the roots of thought and values that form the basis for contemporary science and education.